Cross culture comparison in ethno-pharmacological uses of plants between two geographical regions of Northwest Pakistan - Batool, Rishma; Nazar, Amina; Adnan, Muhammad; Khursheed, Zainab; Mohsin, Fakhar; Hussain, Wahid (Ethnobotany Research and Applications, 2025)
Background: Medicinal plants and plant-based medicines are extensively used in the healthcare system in developing countries. Present research work was carried out to record and report the ethno-pharmacological comparison of medicinal plant uses of two culturally different geographical regions (Kohat and Parachinar) located in the Khyber Pakhtunkhwa province of Pakistan. Methodology: The ethno-pharmacological survey was conducted through a semi-structured questionnaire comprised of demographic information and traditional knowledge of medicinal plants of the localities. The survey was based on traditional ethno-medicinal knowledge of local plants. Relative frequency of citation (RFC), informant consensus factor (ICF), and frequency of citation (FC) were among the quantitative tools used to assess the information that was collected. Results: A total of 103 medicinal plants were reported in two geographical regions, Kohat and Parachinar. Out of these, 62 medicinal plants were reported from District Kurram Parachinar and 41 from District Kohat. In total, 14 medicinal plant species were common based on reported names and traditional knowledge between the two regions. Based on their local names, therapeutic applications, dosage, treatment, and preparation methods, eighty-nine (89) species were determined to be unusual. Among all reported species highest RFC value was reported for Withania coagulans. In the case of ICF gastrointestinal diseases marked maximum value 730 use report. Leafs reported that most plant parts were utilized during the survey. Conclusion: In terms of the components of medicinal plants employed, their local names, and their traditional uses, there was a notable 91.67% difference between the two localities. This suggests that the ethnobotanical knowledge of the two locations differs, reflecting differences in environmental effects and cultural behaviors. These variations show how diverse traditional medicine is in each place and emphasize how crucial it is to record and preserve this distinctive legacy. Keywords: Ethno-pharmacological uses, medicinal plants, cross-culture, Kohat, Parachinar.